Strategi Pengembangan dan Pemasaran Digital Industry Agency - Yasid, Idham Fakhri; Pahlevi, Reza Widhar (CV. Kurnia Grup, 2024)
This research aims to report on the development of Digital Industry Agency (DIA), covering the company’s identity, organization, target market, and financials. DIA, known for specializing in the development of digital products, focuses on big data and ERP (Enterprise Resource Planning) systems. The goal of establishing DIA is to address various issues within companies related to Industry 4.0 through digitalization. ERP, as the main product, is designed to enhance company efficiency and effectiveness by integrating systems and business processes into a unified platform that can be used by all departments and branches of the company. DIA has successfully overcome challenges in developing and marketing digital solutions, particularly ERP, in the era of Industry 4.0. By focusing on innovation and digitalization, DIA has been able to improve operational efficiency and expand its market reach. The strategy of combining digital technology with service personalization has proven effective in attracting and retaining customers. To maintain its position as a leader in Indonesia's digital industry, DIA is advised to continue investing in advanced technology, human resource training, and product innovation to stay competitive and relevant in the market. Sustained investment in technology and product development will ensure DIA remains a key player in an ever-evolving market.